India in the new south asia : strategic, military and economic concerns in the age of nuclear diplomacy - Jain, B. M. (New Delhi : Viva Books, 2011)
In recent years, South Asia has become a flashpoint of conflict between the nuclear powers of India and Pakistan over the interconnected problem of Kashmir and cross-border terrorism. B. M. Jain here re-evaluates India's security, strategic and nuclear policy in the new South Asia of the post 9/11 era. He also provides a reappraisal of the regional security implications of India's turbulent relationships with Pakistan, Nepal, and Bangladesh. Furthermore, he examines the strategic engagement of America, Russia and China with South Asian states. This book will be invaluable for public policy-makers, researchers, and undergraduate and graduate students of South Asian studies.
Keywords: India; International relations; National security; Nuclear weapons